Disseminação da gonorreia e Covid-19: estudo de dois cenários epidemiológicos - Pedroso, João Marcos Cavalcante (Universidade Federal de São Carlos, 2025)
This work presents mathematical models for two diseases that do not confer permanent immunity after infection: gonorrhea and Covid-19. In the case of gonorrehea, non linear differential equations are introduced to describe the dynamics between susceptible an infected individuals in a population. We analyze the stability of equilibrium points and conditions leading to extinction or endemic persistence. Subsequentely we address Covid-19 using data analyze from São Carlos - SP. Instead of employing a classical compartimental moldel, we resortto a logistic curve to describe the ccumulated number of cases, discussing how this type of fit can represent the temporal avolution in a relatively simple manner. The study demonstrates how mathematical analysis can contribute to understanding the trajectories of infectious diseases and their implications for public health.
Spread of gonorrehea and Covid-19: study of two epidemiological scenarios
Keywords: Epidemiologia; Modelagem matemática; Gonorreia; Covd-19; Epidemiology; Mathematical modeling; Gonorrhea; Logistic curve; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE::EQUACOES DIFERENCIAIS PARCIAIS